Composition and distribution characteristics of acetic acid-related bacteria during the fermentation process of strong-flavor baijiu - Mandlaa Mandlaa; Mengyu Liu; Guojun Ren; Hui Qu; Hui Wang; Fei Ma; Min Zhang; Jing Guo; Zhongjun Chen; Ziyu Sun (Frontiers in Microbiology)
Ethyl acetate (EA) has an important impact on the quality of Strong-flavor Baijiu (SFB) and is synthesized from acetic acid (AA) and ethanol by microorganisms during the fermentation process. However, the composition and distribution characteristics of AA-related microorganisms are unclear in the SFB production process. In this study the changes of bacterial community and concentration of AA during the fermentation process (7-67d) and different season fermentation (spring and summer) was investigated, and the composition of AA-related bacteria was analyzed to reveal the distributional characteristics of AA-related bacteria in brewing environment (Daqu, raw materials, pit mud, ground and tools). The results showed that the concentration of AA increased during the fermentation process, and AA in summer was significantly higher than in spring (p < 0.05). A total of 23 genera were significantly related to AA (p < 0.05), and most of them were also significantly related (p < 0.05) to the dominant genus, reducing sugar, moisture, and acidity. Moreover, Pantoea (negatively related to AA) mainly comes from DaquF and was the dominant genus during the fermentation process. Saccharopolyspora, Lactococcus, and Streptomycetaceae had low abundance and a negative relationship with bacteria mainly found in DaquL and pit mud. Unclassified_Bacilli had a positive relationship with AA and mainly came from raw material. Ground and tools can provide seven genera with low relative abundance. This study lays a foundation for establishing methods to regulate AA in SFB.